“Student’s Passion on Entrepreneurship (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam, IAIN Purwokerto) - Sochimin socha (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2017)
ABSTRACT The aim of this study was to determine whether is minimum of one variables influence from personality, family environment, opportunities, and incomes towards entrepreneurship interest student of the Faculty of Economics and Business of Islam, IAIN Purwokerto. Data used in this research is primary data through questionnaire, interview, and observation. The sampling technique is Purposive Sampling which is calculated with Slovin formula’s. The data analysis by quantitative with multiple linear regression method using SPSS 17.0 for windows. The result of this study shows that personal variable, famlily environment, opportunities, and incomes is take effect simultaneously on entrepreneurship interest student of the Faculty of Economics and Business of Islam, IAIN Purwokerto. Partially, personal variable, and opportunities isn’t effect to entrepreneurhip interest student the Faculty of Economics and Business of Islam, IAIN Purwokerto, and family environment variable, and incomes is take effect to entrepreneurhip interest student the Faculty of Economics and Business of Islam, IAIN Purwokerto. The result of this reseach in a determination coefficient amont 0,79%, the mean is 79% variation entrepreneurship interest student the Faculty of Economics and Business of Islam, IAIN Purwokerto can be explain with independent variable which cover personality, family environment, opportunities, and incomes, and the rest explained by other varibles outside the regression model. Keywords : Personality, Family Environment, Opportunities, Incomes, Entrepreneurship Interest, Entrepreneurship.